2010
DOI: 10.1021/cg900868t
|View full text |Cite
|
Sign up to set email alerts
|

Nucleation and Early Stage Crystallization of Fluorapatite in Apatite-Mullite Glass-Ceramics

Abstract: The crystallization morphology and activation energy of fluorapatite formation in apatite-mullite glass-ceramics has been examined. A systematic change in the amount of network modifier in the base glass has demonstrated that increasing levels of network modifier cause a corresponding increase in activation energy for fluorapatite crystallization and a decrease in fluorapatite crystal size. Apatite-mullite glass-ceramics are known to phase separate and nucleate prior to crystallization. To separate these effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“…This composition may produce crystal sizes and spatial density similar to the topographies used by Dalby et al [11]. Some of the glass was re-melted and cast to form cylinders (Ø 11 mm) with annealing at Tg − 100 °C (560 °C) [14]. Cast cylinders were sectioned into 2.5 mm thick discs.…”
Section: Methodsmentioning
confidence: 98%
See 3 more Smart Citations
“…This composition may produce crystal sizes and spatial density similar to the topographies used by Dalby et al [11]. Some of the glass was re-melted and cast to form cylinders (Ø 11 mm) with annealing at Tg − 100 °C (560 °C) [14]. Cast cylinders were sectioned into 2.5 mm thick discs.…”
Section: Methodsmentioning
confidence: 98%
“…A glass with molar composition 4.85SiO2-3.25Al2O3-1.5P2O5-3.25CaO-1.75CaF2, chosen following a review of previous studies [14,16,17], was synthesised by melt-quench, as previously described [5,14]. This composition may produce crystal sizes and spatial density similar to the topographies used by Dalby et al [11].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…These results were expected as fluoride facilitates crystallization occurrence. However, it has been shown that the activation energy of crystal growth is proportional with increasing CaF 2 content due to its influence on phase separation and nucleation density [25]. The effects of CaF 2 on peak crystallization and sintering windows of glass series are presented in Fig.…”
Section: Xrdmentioning
confidence: 99%